Severe Chlamydia psittaci pneumonia complicated by deep vein thrombosis: a case report - Zhang, Anbing; Huang, Ting; Lao, Xiaoli; Ma, Jun; Xia, Xiuqiong; Liang, Jianping (Frontiers in Medicine, 2025)
Deep vein thrombosis (DVT) of the legs is a rare but clinically important complication of Chlamydia psittaci pneumonia. We report a case of a 51-year-old man who was admitted to the hospital with fever, cough, and dyspnea. Next-generation sequencing confirmed the diagnosis of Chlamydia psittaci pneumonia. His D-dimer level was elevated on admission, and ultrasound confirmed DVT in the legs. The patient was treated with intravenous doxycycline for the infection and rivaroxaban as an anticoagulant. His condition gradually improved and he was discharged after making a full recovery. In this paper, we explore the potential association between Chlamydia psittaci infection and venous thrombosis, as well as clinical management strategies.